2010
DOI: 10.3201/eid1609.100459
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Rats and House Sparrows as Hosts for North and South American Strains of Eastern Equine Encephalitis Virus

Abstract: TOC summary: Wild rodents and wild birds can serve as amplification hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…This finding, together with the discovery of early season EEEV infections in pools of mosquitoes that feed primarily upon ectothermic hosts provides support to the hypothesis that EEEV may overwinter in seasonal foci in ectothermic vertebrates. These data also reinforce recent studies 7 that suggest other animals in addition to birds may play an important role in the dynamics of the EEEV enzootic transmission cycle.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This finding, together with the discovery of early season EEEV infections in pools of mosquitoes that feed primarily upon ectothermic hosts provides support to the hypothesis that EEEV may overwinter in seasonal foci in ectothermic vertebrates. These data also reinforce recent studies 7 that suggest other animals in addition to birds may play an important role in the dynamics of the EEEV enzootic transmission cycle.…”
Section: Discussionsupporting
confidence: 79%
“…25 Recent studies have demonstrated that cotton rats may serve as reservoirs for both North American and South American strains of EEEV. 7 Interestingly, the South American strains of the virus seemed to replicate to higher titers in cotton rats than did the North American strain and the South American strains were less pathogenic to cotton rats than the North American strain. 7 These data suggested that while both North American and South American strains of the virus were capable of using cotton rats as a reservoir, the South American strain might be better adapted to a small mammal reservoir than North American strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to EEEV, some avian species that were previously recorded to be EEEV-seropositive in Trinidad (Tikasingh, 1968(Tikasingh, , 1973(Tikasingh, , 2004 were negative in the current study. Considering reports that both birds and rodents become viremic after EEEV infection (Arrigo et al 2010), a larger sample of avian and rodent sera, as well as a more focused survey in EEEV-and VEEV-positive locations, may prove useful to gain further insight into the local circulation and maintenance of these viruses.…”
Section: Discussionmentioning
confidence: 99%